MODEL PENGEMBANGAN PAKET TRAINING BAGI KARYAWAN PENYEDIA JASA AKOMODASI DI KABUPATEN MOROWALI UTARA PROVINSI SULAWESI TENGAH - Lagarense, Bet El; Wijanarko, Sony; Maukeno, Dinda A. N. (Jurnal Hospitaliti, 2023)
Hotels are one of the main destinations for guests not only because of the management used but the service strategy for guests is very important, namely how to impress customers with the service provided by employees. The question for us is whether it is true that the level of customer comfort and satisfaction is determined by hotel class? That the higher the class of the hotel, the more satisfied customers are? The question above can be said to be correct and it can also be said to be wrong, because it can be said that one of the factors that plays the most role in customer satisfaction and comfort is the service they receive when using hotel facilities, so in this case it can be said that the completeness of hotel facilities and service support provided The goodwill of the employees will have a good impact on customer satisfaction and the image of the hotel itself in the eyes of customers. In North Morowali Regency itself there are several inns, hotels and motels which are still lacking in terms of service.